Comparison of Hemoglobin Levels of Nasopharin Cancer Patients Before and After Radiation in Radiotherapy Installations RSUD Prof. Dr. Margono Soekardjo - Ermi Susi Yanti; Tantri Analisawati Sudarsono; Arif Mulyanto; Linda Wijayanti (Science Midwifery, 2022)
Hemoglobin levels can be used as an indicator of a decrease in a person's nutritional status. Radiotherapy can result in a decrease in nutritional status in nasopharyngeal cancer patients. This study aims to prove the existence of differences in hemoglobin levels in nasopharyngeal cancer patients before and after radiotherapy. This study used a retrospective design, based on medical record data of nasopharyngeal cancer patients who were treated at rsud Prof. Dr. Margono Soekardjo January – May 2022 Data analysis in this study includes descriptive analysis and hypothesis testing. Test the hypothesis using the T Dependent test with normal distributed data. The degree of meaningfulness is p ≤ 0.05. The research data is normally distributed so that the T Dependent test is used. A meaningful comparison of hemoglobin levels was obtained in patients with nasopharyngeal cancer before and after radiation with p 0.003 So it can be concluded that there is a significant comparison with hemoglobin levels in nasopharyngeal cancer patients before and after radiation at rsud Prof. Dr. Margono Soekardjo.